Development of Codular-Assisted Android-Based Mathematics Media to Increase Student Motivation and Learning Outcomes - Permatasari, Nova Mitha; Effendi, Moh. Mahfud; Azmi, Rizal Dian (Universitas Muhammadiyah Mataram, 2023)
Research on the development of codular-assisted android-based mathematical media was carried out to increase student motivation and learning outcomes in learning mathematics. This research refers to the ADDIE model, which consists of 5 stages: analysis, design, development, implementation, and evaluation. The research was conducted on 30 class IX students at MTS Muhammadiyah 1 Malang. The study results show that the validity value of the media is 88.4%, with a very good category. So that this android media meets the criteria and is very suitable for use in learning. As for the test results on student learning outcomes, this media can improve student learning outcomes by increasing the average test results, namely the pre-test 41.67 and the post-test 91.67, which shows that the data results make the data distribution homogeneous. The student learning motivation questionnaire as a whole with the pre-test results found 93.33% who had motivation in the good criteria, and the remaining 6.67% were in the fewer criteria. In the post-test, 83.33% had very good motivation, and the remaining 16.67% were in good criteria. This shows an increase in student motivation after using Android-based media. So it can be concluded that the use of android-based mathematics media with the material Build a Curved Side Room (Tube) developed in this study is valid and can increase motivation and student learning outcomes. This study proves that learning media can increase motivation and learning outcomes. Therefore, the results of this study can be used as an alternative to learning mathematics, especially to increase student motivation and learning outcomes.